PERSONAL BRANDING GIBRAN RAKABUMING RAKA DALAM KAMPANYE PILKADA SOLO DENGAN PENGGUNAAN MEDIA BARU - Abdurrachman Zhafir Riasaptarika; Muhammad Aedil Akbar; Ninda Puspita Dewi (Pusat Penelitian dan Pengabdian Masyarakat, Politeknik Negeri Batam, 2021)
The use of new media in political communication that is more today is the trend in the government, internet campaigns, online citizen political communication, as well as horizontal relations between citizens and other citizens, both in the form of virtual groups and in the context of political education between citizens. Ahead of the election, a number of educated community groups will emerge seeking to strengthen citizens' political awareness through online dissemination of political information targeting netizens. In the current era, various communication media are used to convey political messages including new media. What is the important role of social media in political communication? What is the role of social media in political communication? One of the roles of social media is to form personal branding as a person or a group. Personal branding is more about desires, skills, goals, and values. It is the result of one's hunt for fulfillment and meaning. Personal branding becomes ammunition in building the character of Gibran in this case because the authenticity of branding oneself helps minimize one's weaknesses. So it can be concluded that, first, Gibran's personal branding by utilizing all social media platforms has succeeded in building an image and generating public opinion that he is able to take advantage of advances in new media technology. Second, the COVID-19 pandemic and the presence of new media have drastically changed the political campaign system so campaign innovation in the COVID-19 pandemic era built Gibran's brand as a young politician. He was able to adapt to conditions and challenges in various conditions.